An echo in the bone [compact disc, unabridged] : a novel - Gabaldon, Diana (Gabaldon, Diana. Outlander novels., 2009)
In the seventh installment of Diana Gabaldon's Outlander series, Jamie Fraser and his time-traveling wife Claire face an abundance of daunting obstacles in the midst of the American Revolution. While they already know how history will play out, they are uncertain of their own futures.